Britain, Southeast Asia and the onset of the Cold War, 1945-1950 - Tarling, Nicholas (Cambridge University Press, 1998)
This book talk about the detailed and original study throws new light on the evolution of British policy in Southeast Asia in the turbulent postwar period. It is a major contribution to the diplomatic and political history of Southeast Asia.